Evaluation of fatigue, load and the quality of chest compressions by bystanders in hot and humid environments - Haruka Takahashi; Kensuke Suzuki; Yohei Okada; Satoshi Harada; Hiroyuki Yokota; Marcus Eng Hock Ong; Satoo Ogawa (Resuscitation Plus)
Background: This study aimed to investigate the physiological load on bystanders during cardiopulmonary resuscitation (CPR) and the quality of chest compressions in hot and humid environments. Methods: This prospective experimental study compared the physical load and quality of chest compressions among healthy volunteers who performed 10 min chest compression in a climate chamber under normal conditions (for Tokyo) (Wet Bulb Globe Temperature [WBGT] 21 °C) and hot and humid conditions (WBGT 31 °C). The primary outcome was the depth of chest compressions over a 10-minute period. Secondary outcomes included the volunteer’s heart rate (HR), core body temperature (BT), Borg scale for assessing fatigue, and blood lactate levels. Data were analyzed using two-way repeated measures analysis of variance (ANOVA) and paired t-tests. Results: Out of 31 participants, 29 participants (mean [SD] age: 21[0.7], male: 21 [70.5 %]) were included in the analysis. For WBGT 21 °C and 31 °C, the mean chest compression depth at 10 min was not statistically difference (the depth of chest compression: 52.2 mm and 51.5 mm (p = 0.52)). At 10 min, heart rate and core temperature were 126 vs. 143 bpm, and 37.4℃ vs. 37.5℃ for WBGT 21℃ vs. WBGT 31℃ (mean differences: 17 bpm [95 % CI: 7.7–26.3], 0.1℃ [95 % CI: −0.1–0.3]). At the end, Borg scale was 16 vs. 18 and lactate levels were 3.9 vs. 5.1 mmol/L (mean differences: 2 [95 % CI: 1–3], 1.2 mmol/L [95 % CI: 0.1–2.3]). Conclusion: there was no significant difference in the depth of chest compression of paramedic students under the conditions between WBGT 31℃ and WBGT 21℃. For secondary outcomes, the lactate and fatigue of bystanders increased under WBGT 31℃ compared to WBGT 21℃. Further research is needed on CPR in hot and humid environments.